Contemporary environmental principles: from human dignity to the risk society (Revista do Tribunal Regional Federal da 3ª Região, 2021)
This article aims to study the principle of Environmental Law and its application in view of the peculiarities of the so-called risk society and how the environment is related to this model of society. With the emergence of new risks, the Law must create instruments that mitigate possible environmental damage, which must be done in favor of development. Considering the peculiarities of the environmental legal good within this new context, it appears that the principle of prevention and the principle of precaution are important instruments for risk management, creating control mechanisms and discerning the notions of what is allowed and what is acceptable. Allied to the classic principles, among them the dignity of the human person, the importance of prevention and precaution in its ethical and legal dimension is analyzed with a view to the realization of a sustainable environment for present and future generations.
Keywords: environmental law; envionmental principles; risk society; prevention; precaution